A Rare Case of Watery Vaginal Discharge due to Caesarean Scar Dehiscence following Brace Suture and Balloon Tamponade for the Management of Postpartum Hemorrhage - Krystal Koh; Devendra Kanagalingam; Rajeswari Kathirvel (Case Reports in Obstetrics and Gynecology)
A woman in her early twenties with dichorionic diamniotic twins underwent emergency caesarean section (CS) for failed induction of labor for discordant growth at 37 weeks. Her CS was complicated by atonic postpartum hemorrhage (PPH) requiring uterotonics, B-lynch suture, and Bakri balloon. She presented on the 5th postoperative day (POD) with fever and wound pain and collapsed due to desaturation. Investigations confirmed ascites on computed tomography (CT) of her abdomen and cardiomyopathy on echocardiogram. She was readmitted on the 22nd POD with watery vaginal discharge. CT abdomen revealed a dehisced CS scar and loculated ascites. Her discharge settled after three weeks with antibiotics and drainage of the ascites. A CT scan 3 months later showed reduction of the peritoneal collection. Caesarean scar dehiscence should be considered for patients presenting with ascites and vaginal discharge after a CS, particularly in the presence of risk factors such as infection or anemia.